2016
DOI: 10.1007/978-3-319-42468-2_9
|View full text |Cite
|
Sign up to set email alerts
|

The Nutrition Transition in Developing Asia: Dietary Change, Drivers and Health Impacts

Abstract: This chapter reviews the likely consequences of dietary change for human health and wellbeing in Asia where a transition is occurring from diets dominated by low fat, high fibre foods to increased consumption of processed and packaged convenience foods. These foods are higher in fats, sugars and salt and are linked to increased rates of diet-related non-communicable disease. The chapter traces between-country differences and considers the drivers of dietary change including economic growth and rising incomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 25 publications
5
59
0
10
Order By: Relevance
“…In spite of not assessing the essential characteristics of each of the nutrition transition stages, the evidence suggests that the country, and particularly the urban Dushanbe, is moving to stage 4, degenerative disease (30) . This stage is characterised by an increased consumption of processed beverages and food rich in sugar and fat, associated with the evolution of food-transforming technologies, and a decreased consumption of nutrient-dense food such as fruits and vegetables (1,4) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of not assessing the essential characteristics of each of the nutrition transition stages, the evidence suggests that the country, and particularly the urban Dushanbe, is moving to stage 4, degenerative disease (30) . This stage is characterised by an increased consumption of processed beverages and food rich in sugar and fat, associated with the evolution of food-transforming technologies, and a decreased consumption of nutrient-dense food such as fruits and vegetables (1,4) .…”
Section: Discussionmentioning
confidence: 99%
“…fruits, vegetables, legumes and whole grains) and a concomitant increase in the consumption of processed food, more likely to be energy dense, rich in fat, sugar and salt (2) . This transition is ongoing in Central Asia and, specifically, in Tajikistan (3) where increased consumption of processed food and soft drinks has been reported (4) .…”
mentioning
confidence: 99%
“…One study reported that 62% of the world's overweight or obese population now resides in developing countries (Ng et al., ). The reasons for increasing obesity rates in the developing world include urbanization (Mendez & Popkin, ), rising incomes (Dinsa, Goryakin, Fumagalli, & Suhrcke, ), media (Ferguson et al., ; Prentice, ), time poverty (Kelly, ), American junk food (Norris, ), and processed food exports (Jacobs & Ritchel, )—all related to globalization.…”
Section: The Developmental Psychology Of Globalizationmentioning
confidence: 99%
“…Caloric intake Calories ijk , is a continuous variable representing average daily (3-d average) caloric intake in kilocalorie (kcal) from all food items consumed over a 24-h period by individual i, living in household j, in city k (see equation (1)).…”
Section: Outcome Variablesmentioning
confidence: 99%